Direct Observation Techniques Using Scanning Electron Microscope for Hydrothermally Synthesized Nanocrystals and Nanoclusters - Asano, Natsuko (Nanomaterials (Basel), 2021)
Metal oxide nanocrystals have garnered significant attention owing to their unique properties, including luminescence, ferroelectricity, and catalytic activity. Among the various synthetic methods, hydrothermal synthesis is a promising method for synthesizing metal oxide nanocrystals and nanoclusters. Because the shape and surface structure of the nanocrystals largely affect their properties, their analytical methods should be developed. Further, the arrangement of nanocrystals should be studied because the properties of nanoclusters largely depend on the arrangement of the primary nanocrystals. However, the analysis of nanocrystals and nanoclusters remains difficult because of their sizes. Conventionally, transmission electron microscopy (TEM) is widely used to study materials in nanoscale. However, TEM images are obtained as the projection of three-dimensional structures, and it is difficult to observe the surface structures and the arrangement of nanocrystals using TEM. On the other hand, scanning electron microscopy (SEM) relies on the signals from the surface of the samples. Therefore, SEM can visualize the surface structures of samples. Previously, the spatial resolution of SEM was not enough to observe nanoparticles and nanomaterials with sizes of between 10 and 50 nm. However, recent developments, including the low-landing electron-energy method, improved the spatial resolution of SEM, which allows us to observe fine details of the nanocluster surface directory. Additionally, improved detectors allow us to visualize the elemental mapping of materials even at low voltage with high solid angle. Further, the use of a liquid sample holder even enabled the observation of nanocrystals in water. In this paper, we discuss the development of SEM and related observation technologies through the observation of hydrothermally prepared nanocrystals and nanoclusters.